The chase : a novel - Evanovich, Janet; Goldberg, Lee, 1962- (New York Bantam Books, 2014)
Thief and con artist Nicolas Fox has teamed up with FBI Special Agent Kate O'Hare to catch the world's most wanted and untouchable criminals. Their case involves a stolen rare Chinese artifact from the Smithsonian a crime that will torpedo U.S. relations with China if it ever becomes public.
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Government investigators -- Fiction; Women detectives -- Fiction; Swindlers and swindling -- Fiction; Undercover operations -- Fiction; Romantic suspense fiction; Suspense fiction